PENGARUH DUA SPESIES FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN DAN KETAHANAN SEMAI KEMIRI (Aleurites moluccana Willd.) PADA CEKAMAN KEKERINGAN - Amina, Siti; Yusran, Yusran; Irmasari, Irmasari (Warta Rimba, 2014)
A study on the effects of two Fungi Mycorrhizal Arbuscular (FMA) species and watering interval on the growth and resistance of Aleurites moluccana Willd. Seedlings on drought condition was conducted at the farmers group nursery, Uwemanje village, Kinovaro district, Sigi regency, Central Sulawesi. The experiment was laid out in a Randomized Complete Design (RCD) with factorial pattern. First, species ofÂ  FMA consist of three treatments; without mycorrhizal inoculation/control (M0), Gigaspora margarita (M1), Glomus mosseae (M2). Second, watering interval; every day (A0), every three days (A1) and every six days (A2). Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant, fresh weight of shoot and root, dry weight of shoot and root, and seedling quality index. The results showed that interaction between different FMA species and watering interval had significant effect only on the seedling height increment, fresh weight of shoot and root and dry weight of shoot and root, but FMA species and watering interval treatment gave significant difference on the stem diameter increment and increment of leaf number per plant.The highest growth parameters was achieved by Gigaspora margarita inoculation compared to Glomus mosseae and control treatments in all watering intervals. Keywords : Fungi Mycorrhizal Arbuscular, Watering Interval, Seedling growth, Water stress, Aleurites moluccana Willd.